Effect of vacuum aging and influence of sire on palatability of beef longissimus from grass-FED F1 senepol x zebu bulls - Huerta Leidenz, Nelson; Rodas González, Argenis; Smith, Gary (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Fourteen carcasses from grass-fed F1 Senepol crossbred bulls (from 3 Senepol bulls mated to 14 Nellore -influenced cows) were electrically stimulated, and longissimus muscle samples were aged for three periods (2, 7 or 14 d) to study cooking traits, Warner-Bratzler shear force (WBS) values and sensory panel ratings for palatability attributes. Sire affected (P=0.001) WBS values. As compared to control (2 -d aged) steaks, those steaks aged 7 or 14 d cooked slower (P < 0.05), had lower WBS values (P < 0.05), and rated as more tender (P < 0.01), with lesser amounts of connective tissue (P < 0.01), and more intense in flavor (P < 0.01). In the control group, 42.9% of the steaks were classified as Tender (WBS4.98 kg). By d 14, 71.4% of the steaks were Tender, 21.4% Intermediate and 7.1% Tough. Aging of steaks from these grass -fed bulls reduced the proportion of tough steaks from 35.7% (d 2, control) to 21.4% (d 7) and 7.1% (d 14).